The Identification of Potential Microalga as Degradable Agent in the Rubber Waste Water PT. Ricry, Pekanbaru - LUBIS, DAME FLORENSIA; M, Hasbi; ', Budijono (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
The identification of potential microalga as  degradable agent in the rubber  waste water PT. Ricry, Pekanbaru has been done on November to Desember 2013. The aims of these research is understand the composition, abundance and type of dominant microalga in the rubber waste water and environment factors. There were four sampling site namely collecting pool, primary sedimentation pool, secondary sedimentation pool and indicator pool.  Beside phytoplankton, water quality parameter were temperature, TSS, BOD,COD, nitrate, phosphate and ammonia. The result shown 9 famili consist 12 spesies there were Navicula sp., Skeletonema costatum, Coscinodiscus granii, Coscinodiscus stelaris, Chaetoceros contricus, Thalassiosira decipiens, Eureptiella gymnastica, Thalassionema nitchiodes, Pleurosigma capense, Rhizosolenia inbricata, Melosira spaerica and Gyrodinium sp. Based the research there was 3 kinds of microalga can degradable in the rubber waste water is Navicula sp. 5738 sel/l, Skeletonema costatum 5098 sel/l and Gyrodinium sp. 5064 sel/l, its means that microalga have high adaptation and microalga can degradable waste water because it was use the nutrient in the rubber waste water. The high abudance was site in cooleting pool because inlet come from Siak river. The water quality shown tremperature range 28 – 29 0C, pH was 6, DO 2,10 – 2,37 mg/l, BOD 39 – 47 mg/l, COD 43,44 – 63,11 mg/l, TSS 20,33 - 55,67 mg/l, nitrate 1,77 – 2,33 mg/l, phosphate 0,80 – 1,07 mg/l and ammonia 0,78 – 1,54 mg/l. Based on the data obtained, that is microalga use the nutrient in water waste for the grwth and its means microalga can degradable the water waste in rubber so that  it can be concluded that rubber waste water of  PT. Ricry still  below standard. Keywords: microalga, degradable, rubber waste water